Understanding Causation in Healthcare: An Introduction to Critical Realism. (July 2022) - Koopmans, Erica; Schiller, Dr. Catharine
Both healthcare providers and researchers in the health sciences are well rehearsed in asking the question 'What could be causing this'? and examining beyond the surface of observable symptoms or obvious factors to understand what is really occurring with patients and health services. Critical realism is a philosophical framework that can help in this inquiry as we attempt to make sense of the observable world. The aim of this article is to introduce critical realism and explore how it can help both healthcare providers and health science researchers to better understand causation through the mechanisms that generate events, despite those mechanisms often being unseen. The article reviews foundational concepts and examples framed in the healthcare setting to make the key principles, strengths and limitations of critical realism accessible for those who are just beginning their journey with this approach.